The composite face illusion - Murphy, Jennifer; Gray, Katie L. H.; Cook, Richard (Psychonomic bulletin & review, 2017)
Few findings in cognitive science have proved as influential as the composite face effect. When the top half of one face is aligned with the bottom half of another, and presented upright, the resulting composite arrangement induces a compelling percept of a novel facial configuration. Findings obtained using composite face procedures have contributed significantly to our understanding of holistic face processing, the detrimental effects of face inversion, the development of face perception, and aberrant face perception in clinical populations. Composite paradigms continue to advance our knowledge of face perception, as exemplified by their recent use for investigating the perceptual mechanisms underlying dynamic face processing. However, the paradigm has been the subject of intense scrutiny, particularly over the last decade, and there is a growing sense that the composite face illusion, whilst easy to illustrate, is deceptively difficult to measure and interpret. In this review, we provide a focussed overview of the existing composite face literature, and identify six priorities for future research. Addressing these gaps in our knowledge will aid the evaluation and refinement of theoretical accounts of the illusion.